2017
DOI: 10.1111/jgs.14780
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Coronary Artery Bypass Graft Surgery Versus Drug‐Eluting Stents in Older Adults

Abstract: Older adults age 70 to 89 years with left main or multivessel CAD who participated in the BEST, PRECOMBAT, and SYNTAX trials; compared to PCI, CABG was associated with lower risk of primary outcome which was mostly driven by lower risk of myocardial infarction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 22 publications
(65 reference statements)
0
12
0
1
Order By: Relevance
“…During a total of 6.3 (median, 4.9) years of follow-up, the primary composite outcome of all-cause mortality, myocardial infarction, stroke, or repeat revascularization occurred in 26% (141/550) and 34% (179/529) of patients in the CABG and PCI groups, respectively (hazard ratio (HR), 0.75; 95% confidence interval (CI), 0.60-0.94; P =.012). CABG was associated with fewer myocardial infarction (4% vs. 8% for PCI; HR, 0.48; 95% CI, 0.29-0.80; P =.037); and repeat revascularizations (8% vs. 17% for PCI; HR, 044; 95% CI, 0.31-0.64; P <.001), but had little association with all-cause mortality or stroke [11].…”
Section: Discussionmentioning
confidence: 97%
“…During a total of 6.3 (median, 4.9) years of follow-up, the primary composite outcome of all-cause mortality, myocardial infarction, stroke, or repeat revascularization occurred in 26% (141/550) and 34% (179/529) of patients in the CABG and PCI groups, respectively (hazard ratio (HR), 0.75; 95% confidence interval (CI), 0.60-0.94; P =.012). CABG was associated with fewer myocardial infarction (4% vs. 8% for PCI; HR, 0.48; 95% CI, 0.29-0.80; P =.037); and repeat revascularizations (8% vs. 17% for PCI; HR, 044; 95% CI, 0.31-0.64; P <.001), but had little association with all-cause mortality or stroke [11].…”
Section: Discussionmentioning
confidence: 97%
“…An increased rate of myocardial infarctions after PCI was also observed in previous studies in older patients. Older patients aged 70–89 years with LMCA or multivessel CAD who participated in the BEST [18], PRECOMBAT [17], and SYNTAX [19] trials all had reduced rates of the primary composite outcome with CABG, mostly driven by lower risk of myocardial infarction [20]. Although the increased rate of myocardial infarctions after PCI in the group older than 67 years in our study did not translate into differences in all-cause mortality, all reported myocardial infarctions were diagnosed during symptom-driven hospital admissions, indicating a disadvantage for the patient.…”
Section: Discussionmentioning
confidence: 99%
“…However, there have been no randomized trials for comparing the effect of PCI and CABG in very old patients with multivessel disease, such as 3VD. Moreover, results from previous observational studies and pooled-analysis were heterogeneous [ 19 22 ]. Therefore, questions persist concerning the optimal treatment strategy of very old patients with 3VD.…”
Section: Discussionmentioning
confidence: 99%